PENGARUH PENERAPAN XBRL TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris pada Indeks LQ45 di Bursa Efek Indonesia Tahun 2016-2018) - Alberth D. Rupang; Syaikhul Falah; Bill J.C Pangayow (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This study aims to provide empirical evidence about the effect of XBRL implementation on the timeliness of financial reporting of public companies in Indonesia registered in the LQ45 index. The research method uses panel data with 99 observations from 2016 to 2018. The results show that the implementation ofXBRL has a positive and significant impact on the timeliness offinancial reporting, in contrast to the Debt to Equity ratio used to control company leverage has a positive andinsignificant impact on accuracy financial reporting time, as well as Return on Assets used to control the profitability of the company has no significant effect with a negative impact on the timeliness of financial reporting of public companies in Indonesia that are listed on the LQ45 index.